2016
DOI: 10.1371/journal.pone.0167491
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel, Isothiazolonaphthoquinone-Based Small Molecule Activator of FOXO Nuclear-Cytoplasmic Shuttling

Abstract: FOXO factors are tumour suppressor proteins commonly inactivated in human tumours by posttranslational modifications. Furthermore, genetic variation within the FOXO3a gene is consistently associated with human longevity. Therefore, the pharmacological activation of FOXO proteins is considered as an attractive therapeutic approach to treat cancer and age-related diseases. In order to identify agents capable of activating FOXOs, we tested a collection of small chemical compounds using image-based high content sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…As, unlike p53, mutational loss of all FOXOs has not been reported in cancer (40), this would make FOXO an interesting therapeutic target. Our observations that loss of FOXO is detrimental to tumor growth and metastasis were unexpected and might go against the rationale for the development of several small molecules that aim to promote FOXO activity either directly (41) or through inhibition of PI3K/ AKT for cancer therapy (42,43). Although we do not currently know how our observations on the requirement for FOXO extend to other cancer types, it is tempting to speculate that compounds that can inhibit FOXOs could be effective in cancer treatment.…”
Section: Targeting Foxos In Cancer?mentioning
confidence: 81%
“…As, unlike p53, mutational loss of all FOXOs has not been reported in cancer (40), this would make FOXO an interesting therapeutic target. Our observations that loss of FOXO is detrimental to tumor growth and metastasis were unexpected and might go against the rationale for the development of several small molecules that aim to promote FOXO activity either directly (41) or through inhibition of PI3K/ AKT for cancer therapy (42,43). Although we do not currently know how our observations on the requirement for FOXO extend to other cancer types, it is tempting to speculate that compounds that can inhibit FOXOs could be effective in cancer treatment.…”
Section: Targeting Foxos In Cancer?mentioning
confidence: 81%
“…108 Compound 1a (LOM612), a newly synthesized isothiocyanate that is a potent FOXO activator, induces nuclear translocation of FOXO1 and increases the activity of FOXO1 in a dosedependent manner in U2OS osteosarcoma cells and shows a potent antiproliferation and tumor-suppressing effect. 109 Moreover, there is study already stresses this point regarding the role of FOXO1 in clinic. Kim et al studied human gastric carcinoma specimens and revealed that cytoplasmic pFOXO1 expression is positively correlated with the expression of several angiogenesis-related proteins (HIF-1a, NF-jB), compared with normal gastric tissues, suggesting that reduced expression of cytoplasmic pFOXO1 but enhanced expression of nuclear FOXO1 is a potential pathway for cancer treatment.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…Overexpression of FO1–6nls in prostate cancer cells not only blocks Cdk1/2‐induced cytoplasmic localization of FOXO1 but also augments FOXO1's transcriptional activity, thereby contributing to the suppression of prostate cancer . Compound 1a (LOM612), a newly synthesized isothiocyanate that is a potent FOXO activator, induces nuclear translocation of FOXO1 and increases the activity of FOXO1 in a dose‐dependent manner in U2OS osteosarcoma cells and shows a potent antiproliferation and tumor‐suppressing effect . Moreover, there is study already stresses this point regarding the role of FOXO1 in clinic.…”
Section: Prospects and Conclusionmentioning
confidence: 99%
“…FOXO4 expression is higher in muscle, kidney, and colorectal tissue while FOXO6 is primarily expressed in the brain and liver [3,4]. FOXO proteins regulate transcription in the cell nucleus and are involved in the transcription of genes that regulate diverse cellular processes including fuel metabolism, differentiation, proliferation, longevity, cell cycle progression, oxidative stress response, redox signalling and apoptosis [3,5]. Recent studies have shown important tumour suppression activity of forkhead-BOX O transcription factors (FOXOs) by promoting cell cycle arrest, apoptosis and DNA damage repair [6].…”
Section: Introductionmentioning
confidence: 99%
“…Expression site of all these subclasses varies, FOXO1 and FOXO3 is expressed in almost all tissues. FOXO4 expression is higher in muscle, kidney, and colorectal tissue while FOXO6 is primarily expressed in the brain and liver [3,4]. FOXO proteins regulate transcription in the cell nucleus and are involved in the transcription of genes that regulate diverse cellular processes including fuel metabolism, differentiation, proliferation, longevity, cell cycle progression, oxidative stress response, redox signalling and apoptosis [3,5].…”
Section: Introductionmentioning
confidence: 99%